PENERAPAN ASAS MENCARI KEBENARAN MATERIIL PADA PERKARA PERDATA DALAM PERSPEKTIF HUKUM PEMBUKTIAN PERDATA - Lonna Yohanes Lengkong (Fakultas Hukum Universitas Kristen Indonesia, 2017)
In business practice, the agreement is something fundamental matter aimed to protecting the rights of businesses in doing business. The implementation of business agreements it’s became disputes later taken to court to be decided by the judge to protect the rights of businesses. In practice, the judge in deciding civil cases implement the principle of seeking truth material, which is seeking the judge’s conviction, in addition to still use the principle of seeking formal truth in deciding a civil case. Results of the research is the judge assessing evidence submitted by the plaintiff turned out to have applied the principle of seeking truth material by putting the judge’s conviction, obtained by deepening the witness testimony in the trial, although formally evidence have been met and sufficient. Judge indeed should to apply the principle of truth material in order to find the formal truth in deciding a case, it is to convince the judge absolutely convinced before giving the verdict of a civil case. Keywords: Kebenaran Materiil dalam Pembuktian Perkara Perdata